2015
DOI: 10.1111/1348-0421.12291
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium strain expressing OprF‐OprI protects mice against fatal infection by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa poses a major threat to human health and to the mink industry. Thus, development of vaccines that elicit robust humoral and cellular immunity against P. aeruginosa is greatly needed. In this study, a recombinant attenuated Salmonella vaccine (RASV) that expresses the outer membrane proteins fusion OprF 190-342 -OprI 21-83 (F1I2) from P. aeruginosa was constructed and the potency of this vaccine candidate assessed by measuring F1I2-specific humoral immune responses upon vaccination throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Preclinical studies [330,331] and a phase I-II clinical trial [332] involving Salmonella species for the nasal or oral delivery of Pseudomonas OprF or OprI, induced IgG and IgA antibodies. In contrast, in murine models, subcutaneous vaccination with an S. Typhimurium LH430 expressing OprF-OprI achieved the highest levels of protection and specific immunoglobulin titres than oral immunisation [333]. Importantly, a recent study, where an attenuated S. Typhimurium expressing S. enterica type III secretion effector protein, SseJ, and the P. aeruginosa PcrV elicited detectable levels of antigen-specific IgG in all mice, reduced bacterial loads in the spleens and lungs and the levels of proinflammatory cytokines (TNF-α and IL-6) and most of the vaccinated mice survived.…”
Section: Adjuvants In Vaccines Against P Aeruginosamentioning
confidence: 79%
“…Preclinical studies [330,331] and a phase I-II clinical trial [332] involving Salmonella species for the nasal or oral delivery of Pseudomonas OprF or OprI, induced IgG and IgA antibodies. In contrast, in murine models, subcutaneous vaccination with an S. Typhimurium LH430 expressing OprF-OprI achieved the highest levels of protection and specific immunoglobulin titres than oral immunisation [333]. Importantly, a recent study, where an attenuated S. Typhimurium expressing S. enterica type III secretion effector protein, SseJ, and the P. aeruginosa PcrV elicited detectable levels of antigen-specific IgG in all mice, reduced bacterial loads in the spleens and lungs and the levels of proinflammatory cytokines (TNF-α and IL-6) and most of the vaccinated mice survived.…”
Section: Adjuvants In Vaccines Against P Aeruginosamentioning
confidence: 79%
“…Due to the highly immunogenic nature of OprF, numerous studies have utilized the porin in pursuit of a P. aeruginosa vaccine (85,86). Many recent publications involving the administration of chimeric OprF fusion proteins have demonstrated acquired immunity to P. aeruginosa can be achieved in mammals (87)(88)(89)(90)(91). Hassan et al demonstrated that a recombinant trivalent OprF-OprI-flagellin vaccine significantly reduced mortality resulting from acute pneumonia in mice infected with mucoid and nonmucoid strains of P. aeruginosa (89).…”
Section: Intruder Alert: Oprf In Virulence and Immune Responsementioning
confidence: 99%
“…One clinical study in healthy volunteers found oral or intranasal administration of live attenuated Salmonella expressing OprF-OprI antigens led to a significant rise in specific IgA and IgG in the lower airways [ 111 ]. Consequently, further preclinical studies in mice using OprF-OprI [ 112 ] and one study using components of the T3SS [ 113 ] enhanced survival, reduced bacterial growth, and led to overall lower levels of pro-inflammatory cytokines.…”
Section: New Developments In P Aeruginosa Vaccinologymentioning
confidence: 99%